-3(2x+2)-1=5(x+1)+3x

Simple and best practice solution for -3(2x+2)-1=5(x+1)+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2x+2)-1=5(x+1)+3x equation:



-3(2x+2)-1=5(x+1)+3x
We move all terms to the left:
-3(2x+2)-1-(5(x+1)+3x)=0
We multiply parentheses
-6x-(5(x+1)+3x)-6-1=0
We calculate terms in parentheses: -(5(x+1)+3x), so:
5(x+1)+3x
We add all the numbers together, and all the variables
3x+5(x+1)
We multiply parentheses
3x+5x+5
We add all the numbers together, and all the variables
8x+5
Back to the equation:
-(8x+5)
We add all the numbers together, and all the variables
-6x-(8x+5)-7=0
We get rid of parentheses
-6x-8x-5-7=0
We add all the numbers together, and all the variables
-14x-12=0
We move all terms containing x to the left, all other terms to the right
-14x=12
x=12/-14
x=-6/7

See similar equations:

| -9.8*150^2/2*x^2=500 | | -12+5=4-(14x-7) | | 2n=2n-3 | | 12y-2=6 | | 2x-8.6/2=-2.3 | | 4x+7=213x | | 5m+9=39m | | 2+5p=4+3p | | T=3/4(t-2) | | 2+p=4+3p | | 5(1+4x)-5=80 | | 1/2n+1/2n=-11/6 | | 8=3y-7 | | 12,500=8000(1+r)5 | | 2(4y-9-7)=166-46 | | -4(r+6)=-71 | | 12c+15c^2=0 | | 4(2v-6)-10v=8v-6-10v | | x+x+x=54 | | 19=8x+3+6x | | X^2-4x-122=0 | | 6x^2+23x+10/x+2=0 | | M=1/4b=-3/4 | | X+x×6/100=5300 | | 2/11×x=10 | | x-29-31=0 | | (17b-4)-4(4b+3)=-2 | | b=7-5 | | 18÷2x(16-9)-11=0 | | 3x-110=2x-40 | | -5=j-14 | | 8(c-1)=7(c-4) |

Equations solver categories